L2 Arabic learners’ processing of Arabic garden-path sentences: a consistent reading pattern - Alseraye, Abdullah M. Seraye (Frontiers in Psychology, 2024)
Purpose: The main purpose of this study was to investigate to what extent the L2 Arabic learners’ reading process are affected by the incomplete representation of speech (the absence of short vowels and diacritics) while reading ambiguous sentences (garden path sentences). Method: With a self-paced reading software program, forty-one non-native male students, aged from 22 to 26, enrolled in King Saud University, participated in reading 44 sentences (followed by reading comprehension questions) representing three reading conditions, plain, vowelized-discretized, and wrongly-vowelized. Results: For the reading times data, the analysis revealed that the GP structure had a significant effect on the reading processes of L2 Arabic learners; it took them longer to read the GP sentences than their non-GP counterparts. For the reading comprehension, the analysis did not reveal any significant differences between the means for the percentages of correct responses. For the comparison between the three reading conditions, a significant difference was found: it took the participants on average less time to read the GP sentences when presented plain, and more time with the incorrect representation. However, their reading comprehension was not affected. Conclusion: In addition to the good-enough model and the nature of Arabic morphology, the reading experience, is a good candidate to start with as an important factor in the interpretation of the ineffectiveness of the GP structure on the reading comprehension process of Arabic readers, in which the segregability of Arabic writing system prepare the readers to emphasize some sensory inputs and ignore others based on their past reading experience.